Stimulating entrepreneurial practices in the public sector: The roles of organizational characteristics - Kim, Younhee (2010)
Unlike the practices of contracting out and privatization, which reduce public sector involvement and responsibility in service provision, public entrepreneurial practices may be one of the best ways to improve government performance and meet citizens' demand efficiently and effectively. This study examines the relationships between organizational characteristics and public entrepreneurship in order to provide empirical support for entrepreneurial practices in state governments in the United States. The study found that most organizational characteristics influence the entrepreneurial behaviors defined as risk-taking, innovativeness, and proactiveness. The findings suggest that organizational structures and strategies in the public sector need to be adjusted to stimulate entrepreneurial activities and culture through opportunity-driven management. -- Reproduced.
Keywords: Public sector; Entrepreneurs